Silver-functionalized Polyurethane Composite Nanofibers for Controlled Release and Antibacterial Application (Journal of Fiber Bioengineering and Informatics, 2018)
In this study, we report a facile approach to develop composite nanofibrous mat for tissue engineeringapplication. Montmorillonite (MMT) nanoparticles were first used to load an antipyretic analgesicdrug, aspirin (ASP). The ASP-loaded MMT nanohybrids were mixed with polyurethane (PU) forsubsequent electrospinning to form drug-loaded PU ⁄ MMT ⁄ ASP composite nanofibrous mats. Thenelectrospun PU ⁄ MMT ⁄ ASP nanofibers were assembled with a bilayer of polyacrylic acid (PAA) andpoly(ethylene imine) (PEI) through electrostatic interaction. Silver nanoparticles have been immobilizedonto nanofibrous mats by in situ complexation and chemical reduction of AgNO_3 solution to formPU ⁄ MMT ⁄ ASP ⁄ Ag nanofibrous mats. The PU ⁄ MMT ⁄ ASP ⁄ Ag composite nanofibrous mats weresystematically characterized using scanning electron microscopy (SEM), Fourier transform infraredspectroscopy, and mechanical testing. In vitro drug release showed that this composite nanofibrousdrug delivery system can effectively mitigate the burst release of the drug and the introduction of MMTcan improve the tensile stress property. Further the antibacterial properties and cytotoxicity evaluationof these mats demonstrate that the PU ⁄ MMT ⁄ ASP ⁄ Ag has a reasonable activity toward the growthinhibition of model bacterium Staphylococcus aureus, and the PU ⁄ MMT ⁄ ASP ⁄ Ag nanofibers displaygood cytocompatibility. In view of its sustained release profile and excellent biocompatibility, thisdouble-loaded drug delivery system may have great prospect in tissue engineering.